24 Predictors of injury among young children in New Zealand. (20th November 2022) - Ghebreab, Luam; Kool, Bridget; Lee, Arier; Morton, Susan
Abstract : Background: In New Zealand (NZ), unintentional injuries pose a major public health threat to children and are one of the leading causes of hospitalisation and death among children. This study aims to explore the longitudinal relationship between a wide range of child, family and environmental factors and the risk of injury among preschool-aged children. Methods: Secondary data analysis was conducted using the Growing up in NZ cohort linked to national Accident Compensation Corporation (NZ's national injury insurance scheme) injury claims. Predictors of injury were identified using the theoretical life-course framework of child injury prevention domains. A multivariable regression model was fitted with the trajectory measures of variables created for the longitudinal analyses. Results: Up to age five, 74% (n=4156/5637) of children experienced at least one injury. Among these children), 28% (n= 1572/5637) had one injury, and 46% (n= 2584/5637) had more than two injuries. Most injuries (76%; n=3156/5637) occurred in the home. Male sex, poor child health, developmental concern and behaviour difficulty were more likely to be associated with higher injury risk. Maternal depressive symptoms, single-parent homes, and living in public housing were also associated with such life events. Conclusion: Interactions between the child and their family and the broader contextual environment are implicated in injury occurrence among children younger than five. Learning Outcomes: Understanding the pathways to the causation of childhood injury is imperative in efforts to mitigate the risk associated with injuries and the development of effective injury prevention policies.